The effects of lattice strain, dislocations, and microstructure on the transport properties of YSZ films. Issue 22 (24th May 2017) - Harrington, George F.; Cavallaro, Andrea; McComb, David W.; Skinner, Stephen J.; Kilner, John A.
Abstract : We report that lattice strain and dislocations play a negligible role on the ionic conductivity of YSZ films. Abstract : Enhanced conductivity in YSZ films has been of substantial interest over the last decade. In this paper we examine the effects of substrate lattice mismatch and film thickness on the strain in YSZ films and the resultant effect on the conductivity. 8 mol% YSZ films have been grown on MgO, Al2 O3, LAO and NGO substrates, thereby controlling the lattice mismatch at the film/substrate interface. The thickness of the films was varied to probe the interfacial contribution to the transport properties, as measured by impedance spectroscopy and tracer diffusion. No enhancement in the transport properties of any of the films was found over single crystal values, and instead the effects of lattice strain were found to be minimal. The interfaces of all films were more resistive due to a heterogeneous distribution of grain boundaries, and no evidence for enhanced transport down dislocations was found.